(untitled) (Research, Society and Development, 2020)
The drug metamizole is a drug widely used by the Brazilian population, mainly due to its pharmacological actions such as analgesics, anti-inflammatory and antipyretic. In Brazil, the three main classes of circulation drugs are considered, being the reference, generic and similar. The quality control of medicines in the pharmaceutical industries is of great importance, as it provides the quality and safety to consumers. In view of the importance of guaranteeing the efficacy of the drug to the population, the present study aimed to evaluate a pharmaceutical equivalence of the three classes of the drug metamizole in a solid pharmaceutical form of tablets and a concentration of 500 mg. The tests carried out followed the methodologies carried out in the 6th edition of the Brazilian Pharmacopoeia, being carried out the identification tests, average weight, hardness, friability, disintegration time and dosage. The results of the analyzes show that the tested ones fulfill the pharmacopoeial specifications and can be derived from pharmacists, therefore, this study reinforces the need for updated research, as well as corroborates with the dissemination of information on this theme.